Exploring digital professionalism. (2nd September 2015) - Ellaway, Rachel H.; Coral, Janet; Topps, David; Topps, Maureen
Abstract: The widespread use of digital media (both computing devices and the services they access) has blurred the boundaries between our personal and professional lives. Contemporary students are the last to remember a time before the widespread use of the Internet and they will be the first to practice in a largely e-health environment. This article explores concepts of digital professionalism and their place in contemporary medical education, and proposes a series of principles of digital professionalism to guide teaching, learning and practice in the healthcare professions. Despite the many risks and fears surrounding their use, digital media are not an intrinsic threat to medical professionalism. Professionals should maintain the capacity for deliberate, ethical, and accountable practice when using digital media. The authors describe a digital professionalism framework structured around concepts of proficiency, reputation, and responsibility. Digital professionalism can be integrated into medical education using strategies based on awareness, alignment, assessment, and accountability. These principles of digital professionalism provide a way for medical students and medical practitioners to embrace the positive aspects of digital media use while being mindful and deliberate in its use to avoid or minimize any negative consequences.